Queen music production and publishing enterprise / Rahmatunisah Hj Hajan... [et al.] - Hj Hajan, Rahmatunisah; Yusof, Nurina; Sapak, Charlen Tiny; Joseph Abbie, Liliana; Majip, Jenifer (Faculty of Administrative Science & Policy Studies, 2006)
Queen Music Production & Publishing Enterprise are located at Ground Floor, Shop Lot 73, block H, Asia City Singgah Mata 4, 88000 Kata Kinabalu Sabah. Our business is producing publishing cassette and CD for the local artist. Date of commencement of our business is on 1st January 2008. the main reason we choose this date are because we need time to investigate and observe the business market, to collect and borrow money as our business modal and also to gain experience and hiring employees for our music business. The market trend for our production and publishing business is quite challenging but currently it seems like its show a positive feedback from public. We recovered that this type of business was less operated by the bumiputera. Nowadays, non-bumiputera is reached much development and this business being monopolized by them. This encourages us to enter in this field of business so that we can compete with them. We also viewed this have potential to go further moreover there are seldom business like this have been done. Besides that we want to promote local artist to expend their talent. We also want to help to promote the local culture in Sabah by produce album regarding to the native language.